Pengaruh minat baca terhadap kepuasan belajar dan dimoderasi variabel kebersihan perpustakaan - Ardiansyah Ardiansyah; Hapsawati Taan; Eka Sartika (Universitas Hamzanwadi, 2022)
The cleanliness of the library is one of the factors that attract students' interest in studying in the library. The condition of the dirty library environment and the lack of supporting facilities make students discourage their intention to study in the library. The cleanliness of the library is a mediator on students' reading interest in their learning satisfaction in the library. This study aims to analyze the effect of reading interest on learning satisfaction and the effect of the moderating variable of library cleanliness in moderating reading interest on student learning satisfaction. This research takes a quantitative approach with the field study method as its methodology and method. The Moderated Regression Analysis model is used together with the Pertial Least Square analysis. The population in this research is students who use the library for reading activities. Simple random sampling technique was used in this research. The results of this study are first, reading interest has an effect on learning satisfaction, second, library cleanliness has an effect on learning satisfaction and third, library cleanliness can mediate the influence of reading interest on student learning satisfaction.